Avaliação da presença de SARS-COV-2 em diferentes superfícies: o papel dos fômites na transmissão da Covid-19 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
COVID-19 is an infectious respiratory disease caused by the new coronavirus (SARSCoV- 2). Its main route of dissemination is from person to person, and can happen in the family environment, hospital, communities and agglomerations. Although contact with fomites (contaminated surfaces) is not considered a primary transmission route, it serves as an important indicator for studies that monitor the environmental presence of the virus in different locations and surfaces, thus identifying the places where the virus spreads the most. Thus, the present study aimed to identify the presence of SARS-CoV-2 on different hospital and non-hospital surfaces for collective use in the city of Santarém-Pará, aiming to define the places where SARS-CoV-2 circulates. For this, 31 samples were collected in different places with large circulation of people. Analyzes were performed using an automated nucleic acid extraction process and amplification of SARS-CoV-2 fragments using the RT-PCR method. In hospital environments, viral fragments of SARS-CoV-2 were found in the reception room, triage room, specialized care room and in the isolation room for patients with COVID-19. The analysis of samples from non-hospital environments identified the presence of the virus in banknotes and coins, in public transport, in public offices, in road and waterway transport terminals and in gyms. The results obtained indicate the presence of the SARS-CoV-2 virus on different types of surfaces in hospital and non-hospital environments, especially in places with large circulation of people, which reinforces the importance of adopting good hygiene practices and frequent use of protective masks.
Keywords: Transmissão; Fômites; COVID-19; SARS-CoV-2; CNPQ:: CIÊNCIAS DA SAÚDE